When Effective Teacher Training Falls Short in the Classroom: Evidence from an Experiment in Primary Schools - Suzanne Bellue; Adrien Bouguen; Marc Gurgand; Valerie Munier; André Tricot (Institute of Labor Economics (IZA), 2023)
While in-service teacher training programs are designed to enhance the performance of several cohorts of students, there is little evidence on the persistence of their effects. We present the two-year results of a large-scale, randomized study of an intensive in-service teacher training program in France: during and after implementation. Our estimates highlight the short-run effectiveness of the training program; it successfully improves students' outcomes but only during the implementation year. A detailed analysis of teachers' outcomes indicates that teachers changed their pedagogical vision and practices but struggled to apply acquired skills to contents not directly covered in the training.
Keywords: I20; 330; in-service teacher training; professional development; teacher effect